Utilizing Additive Manufacturing for Fabricating Energy Storage Components From Graphene-Reinforced Thermoplastic Composites - Raja Subramani; Simon Yishak (Advances in Polymer Technology)
The quest for efficient and sustainable energy storage solutions has prompted exploration into advanced materials that meet stringent mechanical and thermal requirements. This study investigates graphene-reinforced thermoplastic polymers specifically polyether ether ketone (PEEK), polyethylene terephthalate glycol (PETG), and polylactic acid (PLA) fabricated through additive manufacturing techniques. Traditional materials often suffer from limitations in structural integrity, flexibility, and thermal stability, presenting challenges for their application in energy storage. This research aims to evaluate the mechanical properties of these graphene-reinforced polymers to assess their suitability for energy storage components. Using additive manufacturing, test samples were fabricated, and mechanical testing was conducted to evaluate tensile, flexural, and compression strengths. The results indicate that graphene-reinforced PEEK (G-PEEK) exhibits superior mechanical performance, with an ultimate tensile strength of 120 MPa, Young’s modulus of 1700 MPa, ultimate flexural strength of 160 MPa, and ultimate compression strength of 200 MPa, making it an ideal candidate for applications requiring high structural integrity. Graphene-reinforced PETG (G-PETG) offers a balance of strength and flexibility, with an ultimate tensile strength of 55 MPa, while graphene-reinforced PLA (G-PLA) serves as a cost-effective option, despite lower mechanical properties (ultimate tensile strength of 45 MPa).